Improving Photovoltaic Performance of ZnO Nanowires Based Colloidal Quantum Dot Solar Cells via SnO2 Passivation Strategy - Ozu, Shuhei; Zhang, Yaohong; Yasuda, Hironobu; Kitabatake, Yukiko; Toyoda, Taro; Hirata, Masayuki; Yoshino, Kenji; Katayama, Kenji; Hayase, Shuzi; Wang, Ruixiang; Shen, Qing (Frontiers in Energy Research, 2019)
Colloidal quantum dot solar cells (CQDSCs) based on one-dimensional metal oxide nanowires (NWs) as the electron transport layer (ETL) have attracted much attention due to their larger ETL/colloidal quantum dots (CQDs) contact area and longer electron transport length than other structure CQDSCs, such as planar CQDSCs. However, it is known that defect states in NWs would increase the recombination rate because of the high surface area of NWs. Here, the defect species on the ZnO NWs' surface which resulted in the surface recombination and SnO2 passivation effects were investigated. Comparing with the solar cells using pristine ZnO NWs, the CQDSCs based on SnO2 passivated ZnO NW electrodes exhibited a beneficial band alignment to charge separation, and the interfacial recombination at the ZnO/CQD interface was reduced, eventually resulting in a 40% improvement of power conversion efficiency (PCE). Overall, these findings indicate that surface passivation and the reduction of deep level defects in ETLs could contribute to improving the PCE of CQDSCs.